Enabling technologies for mobile services : (John Wiley & Sons, Ltd., 2007)
The expected future evolution of mobile and wireless communication technologies will enable a whole new generation of mass-market-scale ubiquitous services and applications. The challenge now is to research and develop applications and services addressing the true needs of the end-users, and to provide engaging and sustaining added value to them. Enabling Technologies for Mobile Services takes a comprehensive approach on these challenges and provides practical guidelines on building new, innovative applications and services. It shares knowledge gained from a collaborative research project where the methods and technologies were applied and utilised. This book is ideal for professionals working with enabling technologies and service architecture in companies. It will also be of interest to academics and students studying applications/services, enabling technologies and service architectures at the universities and to anyone interested in the general issues surrounding mobile technology.